P506Brugada Syndrome: is the addition of the electrocardiographic risk markers the clue?. (18th June 2020) - Tronconi, A; Carnero, G; Mysuta, M; Bozza, A; Peltzer, M; Labin, B; Gavilan, L; Ramirez, D; Alvarez, M; Gonzalez, J L; Galizio, N
Abstract: Background: Risk stratification in Brugada Syndrome (BS) remains a clinical challenge. Several electrocardiografic (ECG) risk markers had been described, as a spontaneous type 1 Brugada pattern (ST1B), maximal time interval between the peak and the end of the t wave in precordial leads (Tpe Max), the presence of an S Wave on DI, a PR interval (PRi) ≥ 200ms and fragmented QRS (f-QRS). Purpose: Evaluate the association of ECG risk markers with sudden cardiac death (SCD) or appropriate shocks (A-Sh) by implantable cardioverter defibrillator (ICD) in patients (p) with BS. Methods: From a registry of 97 p with BS with a median follow up of 2.3 years (Q1 0.7-Q3 7.8), 12 lead ECG were recorded in every p. QT peak interval (QTp) was measured between the QRS onset and the peak of the T wave. Tpe was calculated between the difference of QT and QTp in precordial leads (V1 to V6). TpeMax was defined as the most prolonged Tpe. If an S-DI was present, duration and amplitude was measured. PRi was measured on DII. Baseline characteristics: Age 44 ± 13 years, male 74 (76%), secondary prevention 2 (3%), malignant syncope 10 (10%), inducible electrophysiology study 22/43 (51%), SCD on first grade family < 35 years 12 (12%) and ICD 34 (35%). A-Sh and SCD were compared among p with ST1B vs no ST1B, TpeMax≥100 vs <100ms, S-DI ≥0.4 vs <0.4ms, S-D ≥0.1 vs <0.1mV, PRi≥200 vs <200ms and presence of f-QRS ≥ 2 spike ≥ 2 leads. Variables that were associated with A-Sh or SCD were combined. For variables with significant difference sensibility (Sen) and specificity (Spe) was calculated. Results: During follow up 6 p presented A-Sh and no p SCD. Results are described in the Table. Conclusion: In our study population, there was a significant higher incidence of A-Sh in p with ST1B, Tpe Max ≥ 100ms and S-DI ≥ 0.1mV. We found that the presence of one ECG risk marker had a high sensibility to predict A-Sh. The presence of the 3 ECG risk markers highly increased specificity to predict A-Sh. Further trials should be carried out to asses if ECG risk markers would allow us to differentiate which asymptomatic patients could benefit from electrophysiological study for risk stratification (high sensibility - One ECG Risk marker) or would benefit from ICD implantation (high specificity - 3 ECG Risk markers).